A revelação na antropologia de René Girard: da mitologia à escatologia - Godoy, Edevilson de (2019)
The thesis develops God’s revelation since the mimetic theory explained by the anthropologist René Girard from the archaic mythology to the Christian apocalypse, with relevance to the Hebrew Bible and, mainly, the historic event of Jesus of Nazareth, from his incarnation to his resurrection. The reflection accompanies the insights of the French philosopher from modern literature to the Greek tragedy, from the Jewish to Christianity, ending at the apocalypse. The thesis defends the sacred and the religion as structural experiences of the evolution process in which the historic cultural construction binds directly to the search of the transcendent. The revelation is inserted in the internal development of the humanization from the prehistory to the Christian Jewish tradition. God and religion are in the alpha and in the omega of the humanity in a dramatic, cathartic, dialect, prophetic and liberating way which is observed from the violent sacred to the eschatology. This long process follows the anthropology categories, approaches the Mystery through the cultural analytic, historical and sociological means. This study also conducts a set of thematic issues such as otherness, the discovering of the sacred, the social function of religion, the news of the Jewish God, and the event of Christ whose fullness of divine and human reveals the sacrificial religion based on the collective lynching of the scapegoat and the human inability to overcome the harmful mimicry as well. Ultimately, the full man is born in the apocalypse by divine intervention. Thus, the mimetic theory was born in the literature, grew up in the Roman Greek classicity, reached maturity in the Hebrew Bible and among the Christian Gospels, and finally will achieve the consummation in the eschatological. The proposal is a contribution on the dialog between theology and religion science, pointing out the universality of the sacred and the religion in human cultures, and emphasizes the importance of the liberating itinerary of the revelation that rescues the victims whose voices have been silenced by the oppression of the majority and, above all, clarifies that violence and sacrifice are human procedures that do not date back to God